The effectiveness and acceptability of multimedia information when recruiting children and young people to trials: the TRECA meta-analysis of SWATs - Peter Knapp; Jacqueline Martin-Kerry; Thirimon Moe-Byrne; Rebecca Sheridan; Elizabeth Coleman; Jenny Roche; Bridget Young; Steven Higgins; Jennifer Preston; Peter Bower; Carrol Gamble; Catherine Stones (NIHR Journals Library, 2023)
Background The information provided to potential trial participants plays a crucial role in their decision-making. Printed participant information sheets for trials have received recurrent criticism as being too long and technical, unappealing and hard to navigate. An alternative is to provide information through multimedia (text, animations, video, audio, diagrams and photos). However, there is limited evidence on the effects of multimedia participant information on research recruitment rates, particularly in children and young people. Objectives The study objectives were as follows: to develop template multimedia information resources through participatory design, for use when recruiting children and young people to trials to evaluate the multimedia information resources in a series of Studies Within A Trial, to test their effects on recruitment and retention rates, and participant decision-making, by comparing the provision of multimedia information resources instead of printed participant information sheets, and comparing the provision of multimedia information resources in addition to printed participant information sheets. Design Two-phase study: multimedia information resources development including qualitative study; user testing study; readability metrics; enhanced patient and public involvement multimedia information resources' evaluation comprising Studies Within A Trial undertaken within host trials recruiting children and young people. Setting United Kingdom trials involving patients aged under 18. Participants Development phase: n = 120 (children and young people, parents, clinicians, trial personnel). Evaluation phase: n = 1906 (children and young people being asked to take part in trials). Interventions Multimedia information resources (comprising text, audio, 'talking heads' video, trial-specific and trial-generic animations). Printed participant information sheets. Main outcome measures Primary outcome: trial recruitment rate comparing multimedia information resource-only with printed participant information sheet-only provision. Secondary outcomes: trial recruitment rate comparing combined multimedia information resource and printed participant information sheet with printed participant information sheet-only provision; trial retention rate; quality of participant decision-making. Results for each trial were calculated and combined in a two-stage random-effects meta-analysis. Results Phase 1 generated two multimedia information resource templates: (1) for children aged 6-11 years; (2) for children aged 12-18 years and parents. In the Phase 2 Studies Within A Trial the multimedia information resources improved trial recruitment, when compared to printed information alone [odds ratio (OR) = 1.54; 95% confidence interval (CI) 1.05 to 2.28; p = 0.03; I2 = 0%]. When printed participant information sheet-only provision was compared to combined multimedia information resource and printed participant information sheet provision, there was no effect on trial recruitment (OR = 0.89; 95% CI 0.53 to 1.50; I2 = 0%). There were no differences between multimedia information resource and printed participant information sheet on trial retention or participant decision-making quality. In a study within a hypothetical trial setting, multimedia information resource-only provision produced higher ratings of 'information was easy to understand' (Z = 3.03; p = 0.003) and 'I had confidence in decision-making' (Z = 2.00; p = 0.044) than printed participant information sheet-only provision. Limitations It was not possible to include data from three Studies Within A Trial in the meta-analysis due to limited sample size, and questionnaire return rates were low, which reduced the strength of the findings. Conclusions Use of multimedia information increased the rate of recruitment to trials involving children and young people compared to standard patient information sheets. Future work There should be further evaluation of the effects of multimedia information on recruitment to trials involving children and young people. It would be valuable to assess any impacts of multimedia information resources on communication between trial recruiters, children and young people, and parents. Study registration This trial is registered as TRECA ISRCTN 73136092 and Northern Ireland Hub for Trials Methodology Research SWAT Repository (SWAT 97). Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 14/21/21) and is published in full in Health and Social Care Delivery Research; Vol. 11, No. 24. See the NIHR Funding and Awards website for further award information. Plain language summary Clinical trials are important to National Health Service care, but it can be difficult to recruit enough people. We do not know enough about how to improve recruitment, especially when trying to recruit children and young people. People are normally told about a trial through printed information, which is often long and complex. Multimedia information (text, audio, cartoons and video) might be a better way of telling people. It is important to test whether multimedia interventions can help. One way of doing this is to run a 'Study Within A Trial' where people receive information in different ways. We created two multimedia interventions, one for parents and young people being asked for consent, and a simpler one for younger children. Some content applied to all trials, and some about the specific trial people were being asked to consider. We designed these by working closely with children and young people, parents and healthcare staff. We tested the multimedia information in six trials (although only three gave us enough data). Children, young people and their parents saw either standard printed information or our multimedia information. We then collected data on their decision-making, trial recruitment and whether people stayed in the trial. Children and young people who saw multimedia information were more likely to be recruited than those who received standard printed information. Once recruited to a trial, people given multimedia or printed information were similarly likely to remain in the trial. People's views on multimedia and printed information were also similar, but this finding could have been affected by small numbers of people returning questionnaires. Our study provides evidence that multimedia information can be used in trials with children and young people and that it increases the number of people who agree to take part, but further work is needed. Scientific summary Background There is insufficient evidence on how we should treat children and young people across a range of health conditions, in part due to a lack of trial evidence. The information provided to potential trial participants plays a crucial role in their decision-making about participation. In most cases, mandated recruitment information is provided to patients as printed participant information sheets, which have received recurrent criticism as being too long and technical, unappealing and hard to navigate. An alternative is to provide information digitally, enabling the use of multimedia information in trial recruitment, that is, through animations, video, audio, diagrams and photos, as well as written text. There is limited evidence on the effects of multimedia participant information on research recruitment rates, particularly in children and young people. Objectives The study objectives were as follows: to develop template multimedia information resources through participatory design, for use when recruiting children and young people to trials to obtain and analyse qualitative data from interviews and focus groups with members of key stakeholder groups (i.e.